1999
DOI: 10.1017/s1461145799001339
|View full text |Cite
|
Sign up to set email alerts
|

The influence of rapid-rate transcranial magnetic stimulation (rTMS) parameters on rTMS effects in Porsolt's forced swimming test

Abstract: To assess the similarity of the behavioural effects of the rapid transcranial magnetic stimulation (rTMS) to those produced by other antidepressant treatments, in particular to repeated electroconvulsive shock (ECS), we carried out experiments on Wistar rats. The effects of a standard ECS procedure (9 daily treatments; the current parameters: 150 mA, 50 Hz, 0.5 s) were compared with 18 d treatment with rTMS of the same field intensity of 1.6 T but with different stimulation frequency (20 or 30 Hz) and a differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Consistent with the response to ECT, TMS has been shown to produce changes in the expression of glial fibrillary acid protein (107). The effect of rTMS on a forced swimming test is also similar to that of ECT with a clear relationship between the magnitude of the rTMS effect and the number and frequency of the stimulations (108). A dose–response relationship has also been shown in the effect of rTMS on apomorphine‐induced hyperactivity in rats, an effect induced both by rTMS and ECT (109).…”
Section: Therapeutic Studiesmentioning
confidence: 92%
“…Consistent with the response to ECT, TMS has been shown to produce changes in the expression of glial fibrillary acid protein (107). The effect of rTMS on a forced swimming test is also similar to that of ECT with a clear relationship between the magnitude of the rTMS effect and the number and frequency of the stimulations (108). A dose–response relationship has also been shown in the effect of rTMS on apomorphine‐induced hyperactivity in rats, an effect induced both by rTMS and ECT (109).…”
Section: Therapeutic Studiesmentioning
confidence: 92%
“…Only in 1 article 52 tests were performed only during the rTMS intervention (in this case the one closest to the end was selected). Specifically, for the short-term evaluation of rTMS efficacy (included in the meta-analysis), the timing of the tests relative to the neurostimulation intervention was as follows: 24 h after the last rTMS session (12 articles 36,[38][39][40][41][42][43][44]47,54,55,57 ); immediately after the last rTMS session (5 articles 37,[48][49][50]53 ); between 24 and 72 h after the last rTMS session (3 articles 45,46,58 ); during the week following the end of the rTMS intervention (2 articles 51,56 ); during the last week of the rTMS intervention (1 article 52 ).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Treated subjects were either models of depression (11 articles 36,38,45,50,[52][53][54][55][56][57][58] or models of other disorders with comorbid depression (3 articles 40,47,51 ) or healthy animal models (9 articles 37,39,[41][42][43][44]46,48,49 ) receiving active rTMS intervention; control subjects were either models of depression or animals modeling other disorders or healthy animals receiving the sham rTMS intervention, respectively. Regarding the models of depression, 8 articles 36,[52][53][54][55][56][57][58] employed the chronic unpredictable mild stress (CUS) model (4-week protocol in 5 articles 36,52,54,57,58 , 3-week protocol in 2 articles 53,55 , 8-week protocol in 1 article 56 ); 1 article 50 applied a modified version of a forced swimming paradigm (10 min daily for 5 days) able to induce a depression-like state durable for 4 weeks without additional swimming; 1 article 45 employed a genetic model, i.e., the Flinders sensitive line (FSL) and its control (the Flinders resistant line, FRL); 1 article 38 applied a lesion to obtain the olfactory bulbectomy model of agitated depression 59 .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Likewise, rTMS has been reported to exert actions in rodent behavioral models of depression similar to the effects of ECS (Table 2). For example, three studies have reported that 7-10 days of rTMS administered as one high-frequency rTMS train per day reduced immobility time in the Porsolt swim task [Fleischmann et al, 1995;Zyss et al, 1997Zyss et al, , 1999. Zyss et al [1999] found that these effects developed more rapidly the higher the rTMS frequency (30 versus 20 Hz) [Zyss et al, 1999].…”
Section: Behavioral Effectsmentioning
confidence: 99%